Hubungan Dukungan Teman Sebaya dan Kelekatan Orang Tua Terhadap Kecerdasan Emosional pada Siswa Sekolah Menengah Kejuruan (SMK) - Purwanto, Rudy; Effy Wardati Maryam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The objective of this research is to determine the relationship between peer support and parental attachment with emotional intelligence in Vocational High School (SMK) students. The variables used in this study are peer support and parental attachment as independent variables (X) and Emotional Intelligence as the dependent variable (Y). The researcher employed a quantitative correlational approach with a sample of 247 students using proportionate stratified random sampling. The research instruments utilized adapted scales for emotional intelligence, peer support, and parental attachment. The emotional intelligence scale was adapted from the Assessing Emotional Scale (AES) with a Cronbach’s Alpha reliability of 0.960, the peer support scale was adapted from the Peer Support Questionnaire (PSQ) with a Cronbach’s Alpha reliability of 0.782, and the parental attachment scale was adapted from the Parental Attachment Questionnaire (PAQ) with a Cronbach’s Alpha reliability of 0.820. The analysis results showed that the variables of peer support and parental attachment simultaneously indicated an R-Square score of 0.170 or 17.0%, suggesting that peer support and parental attachment are related to emotional intelligence by 17%, while the remaining 83% is influenced by other variables or factors outside of this study.